2004
DOI: 10.1136/bjo.2003.040980
|View full text |Cite
|
Sign up to set email alerts
|

Optic neuritis: chemokine receptor CXCR3 and its ligands

Abstract: Aim: To study the involvement of the chemokine receptor CXCR3 and its ligands (CXCL9/Mig, CXCL10/IP-10, CXCL11/ITAC) in optic neuritis (ON). Methods: 30 patients with ON and 10 non-inflammatory neurological disease controls were included. The patients underwent a phlebotomy, lumbar puncture, and MRI scan. CXCR3 expression was studied on blood and cerebrospinal fluid (CSF) T cells by flow cytometry. CXCL9, CXCL10, and CXCL11 were measured in plasma and CSF by ELISA. Results: CSF concentrations of CXCL10, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
(13 reference statements)
4
9
0
Order By: Relevance
“…Additionally, the expression of CXCR3 on peripheral CD4-positive T cells has been reported to correlate with MRI in patients with MS [31]. However, no relation between CXCR3 expression and MRI activity was found in another study [81]. In the CSF of patients with MS, levels of CXCL10 [29,82] and CXCL9 [29] are significantly incremented, and correlate with MRI activity.…”
Section: Cxcr3 and Its Ligandsmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, the expression of CXCR3 on peripheral CD4-positive T cells has been reported to correlate with MRI in patients with MS [31]. However, no relation between CXCR3 expression and MRI activity was found in another study [81]. In the CSF of patients with MS, levels of CXCL10 [29,82] and CXCL9 [29] are significantly incremented, and correlate with MRI activity.…”
Section: Cxcr3 and Its Ligandsmentioning
confidence: 94%
“…In the CSF of patients with MS, levels of CXCL10 [29,82] and CXCL9 [29] are significantly incremented, and correlate with MRI activity. Interestingly, in optic neuritis, CXCR3 expression in the CSF correlated with the increased expression of its ligand CXCL10 and with the presence of oligoclonal bands in CNS, which usually is indicative of MS [81].…”
Section: Cxcr3 and Its Ligandsmentioning
confidence: 98%
“…They also found significantly negative correlations for both CD25 and CD4 regulatory T cells in the CSF with disease activity (Jensen et al, 2004). Sorensen et al (2004) have demonstrated a selective increase in CXCL10 (IP-10), a ligand for the chemokine receptor CXCR3, in the CSF of patients presenting with isolated ON. Sellebjerg et al (2000) found that CIS patients had a greater number of cells in the CSF-secreting antibodies against myelin basic protein and phospholipid protein than controls and that such secretion was associated with disease activity.…”
Section: Immunologic Markersmentioning
confidence: 94%
“…This finding was correlated with increased oligoclonal bands in the CSF. Therefore, they suggest a role for therapy that would block CXCR3 [25]. Finally, a study of four patients from Denver demonstrated the clonal expansion of B cells and plasma cells in association with an antigen-targeted response in their cerebrospinal fluid [26].…”
Section: Pathology and Immunologymentioning
confidence: 99%